Coupled model simulation of the internal wave wakes induced by a submerged body in SAR imaging. Issue 2 (4th March 2022) - Wang, Letian; Zhang, Min; Wang, Liuying
ABSTRACT: The patterns of internal waves are common occurrences in remote sensing images of the ocean. Internal waves are usually induced by undulating terrain on the sea floor or moving sources in the stratified ocean, especially in an offshore sea or straits in which there exists a relatively significant density stratification of the seawater. In this paper, a new method for simulating the synthetic aperture radar (SAR) images of the internal wave wake excited by underwater vehicles is presented. The flow field of the wake is solved directly using the Reynolds averaged Navier–Stokes solver, and the ambient waves on the sea surface are considered as random wind waves. To consider a continuously stratified ocean, a special multiphase flow model is implemented, which can be used to obtain arbitrary stratified structures numerically. To estimate the scattering distribution of the wakes on the sea surface, an improved facet scattering model is proposed, in which the hydrodynamic modulation of the ambient waves by the wake is considered. Based on the results calculated by the scattering model, the velocity-bunching integral is implemented to simulate the intensity of SAR images of a disturbed sea surface having embedded internal wave wakes.